La construction du sens social dans la presse cubaine. À propos de la nomination de la guerre en Ukraine du 24 février 2022 - Biardzka, Elżbieta; Szymaniak, Włodzimierz J. (2024)
The subject of this article is the discourse of the daily press in Cuba produced following the outbreak of the war in Ukraine. The aim is to establish the social meanings constructed around this conflict through the process of nomination. The authors analyze discursive mechanisms from the perspective of how the semantic effect is created and functions. From the constructivist perspective, they admit that the media are not a mirror of reality but build an imago mundi filtered by axiological perspectives and contribute to the creation of social meaning. In methodological terms, the work uses the instrument of linguistic pragmatics, namely the French discourse analysis (based on French school of linguistique de l’énonciation). It becomes apparent that the Cuban press favours the Russian point of view with President Putin as the charismatic leader defending against the alleged revival of Nazism in Ukraine.
Keywords: nomination; discourse analysis; Cuba; press; Russia-Ukraine war